Preparation and photoluminescence enhancement of Au nanoparticles embedded LaPO4:Eu3+ inverse opals. Issue 7 (6th February 2018) - Chai, Zhuangzhuang; Yang, Zhengwen; Huang, Anjun; Yu, Chengye; Qiu, Jianbei; Song, Zhiguo
Abstract: In this work, we present a facile preparation approach of Au nanoparticles embedded LaPO4 :Eu 3+ inverse opal photonic crystals. In the typical preparation process, the transparent LaPO4 :Eu 3+ sol including HAuCI4 was infiltrated into the opal templates. After the sintering, the 10‐20 nm Au nanoparticles were formed in the interior of nano‐sized wall of LaPO4 :Eu 3+ inverse opal and the Au nanoparticles embedded LaPO4 :Eu 3+ inverse opals were obtained. The luminescence of Au nanoparticles embedded LaPO4 :Eu 3+ inverse opal was investigated. The emission peaks located at the 593 ( 5 D0 → 7 F1 ), 618 ( 5 D0 → 7 F2 ) and 698 nm ( 5 D0 → 7 F4 ) from Eu 3+ ions were observed. The 593, 618, and 698 nm emissions of Au nanoparticles embedded LaPO4 :Eu 3+ inverse opals were enhanced in contrast to these of LaPO4 :Eu 3+ inverse opal without the Au nanoparticles, which is from the excitation field enhancement caused by the localized surface plasmon resonance of Au nanoparticles.